EVALUATION OF STUDENT NURSES’ USE OF THE INTERNET AND TECHNOLOGY IN EDUCATION AND SELF-EFFICACY PERCEPTIONS OF COMPUTER USE - Yeter Kurt; Çiğdem Gamze Özkan; Havva Öztürk; Mehmet Görgöz; İhsan Karlı and Cansu Çetinkaya and Elif Kara and Enes Aksu and Kardem Birinci (The Malaysian Journal of Nursing (MJN), 2020)
Background: In today’s technology age, where information technology is rapidly improving, the ability to use technology and information effectively is among the competencies that a nurse should have. Objective: The research was carried out to determine student nurses’ use of the internet, computer, and technology products in education and their self-efficacy perceptions about computer use. Methodology: This descriptive research was carried out with 548 out of 786 student nurses. The data were collected with a questionnaire including students’ demographic characteristics, use of computers and technology products, and a self-efficacy perception scale. Results: Students preferred their lessons about the nursing profession primarily in a laboratory environment (44%), at hospitals (24%), in a simulation center (21%), and in a classroom environment (11%). The students’ mean self-efficacy perception score was found as 36.83±7.72. In terms of using the computer in everyday life, self-efficacy perception scores of male students, fourth-grade students, those who preferred to have their lessons about the nursing profession in the simulation center, and those who often used mobile applications for educational purposes were found higher than those who were female, first-grade students, those who wanted to have their lessons about the nursing profession in the laboratory, and those who used mobile applications only for several times respectively. Conclusion: The self-efficacy level of nursing students regarding computer use was slightly above the middle level, and the self-efficacy level of male and senior students was higher depending on the frequency of being more engaged in technology.